Comparison of the duration of pregnancy in administration of progesterone suppository and Duphaston tablet in pregnant women with preterm labor after stopping delivery process - Marzieh Lotfalizadeh; Zeynab Khademi; Asieh Maleki; Mona Najaf Najafi (Mashhad University of Medical Sciences, 2019)
Introduction: The rate of mortality and complications are greater in preterm neonates.Therefore, preterm delivery should be avoided.This study was performed with aim to compare the duration of pregnancy in the administration of progesterone suppository and Duphaston tablet in pregnant women with preterm labor after stopping delivery process. Methods: This randomized clinical trial was performed on 195 pregnant women aged 18 to 37 years old with single-pregnancy and diagnosis of preterm labor at the gestational age of 24 to 34 weeks with healthy membranes who were admitted to the hospitals of Mashhad University of Medical Sciences in 2018-2019. After treatment of preterm delivery, if the process of delivery was stopped, pregnant women were randomly divided into three groups: (64 in progesterone suppository group, 65 in Duphaston tablet group and 65 in control group). Dydrogesterone was given as a 10 mg tablet twice daily every 12 hours, and progesterone was given as 200 mg suppository daily. The increase in the duration of pregnancy from the start of treatment to delivery, gestational age at delivery and neonatal results including: birth weight, first and fifth minutes Apgar and NICU hospitalization were evaluated. Data were analyzed by SPSS software (version 23) and ANOVA, Kruskal-Wallis, and Chi-square tests. PResults: In comparison of the results of progesterone suppository and Duphaston tablet, mean neonatal weight in progesterone suppository group was 293±115.9 gr higher than Duphaston group (P=0.03). Among progesterone suppository group and Duphaston tablets group compared to control group, the mean increase in the duration of pregnancy was 11.83±2.8 days (P=0.01) and 7.2±2.8 days (P=0.03), the mean weight of infants was 578.9±115.9 gr (P=0.01) and 285.9±115.9 gr (P=0.03), the mean of first minute Apgar score (P=0.003) and fifth minutes Apgar score (P = 0.01) was significantly higher; but the mean age of pregnancy termination was significantly higher in only progesterone suppository group than control (P=0.01) and there was no significant difference in Duphaston tablet group compared to control (P=0.07). Conclusion: Progesterone suppository and Duphaston tablet increased the duration of pregnancy and age of pregnancy termination, neonatal weight and mean of 1 and 5 minutes Apgar score; but progesterone suppository was more effective in increasing neonatal weight compared to Duphaston tablet.